The subgenus Andrena (Micrandrena) (Hymenoptera: Andrenidae) in the Iberian Peninsula - Dardón, María José; Torres, Félix; Ornosa, Concepción (Zootaxa, 2014)
This work presents the results obtained after a revision of the current species of the subgenus Andrena (Micrandrena) Ashmead, 1899 that appear in the Iberian Peninsula. It provides a key to the species, diagnosis, biological data, and comments about the 19 species and 5 subspecies. Additionally, it includes a redescription of five species because their original descriptions were inadequate. Newly reported for the Iberian Peninsula are Andrena floricola Eversmann, 1852 and Andrena strohmella Stöckhert, 1928. This study is the first contribution to resolve certain taxonomic problems in the subgenus Andrena (Micrandrena); however, the use of additional tools like morphometric and molecular characters are recommended in the future to confirm the taxonomic status of Andrena spreta Pérez, 1895.